Giant Mass in The Right Atrium Originating from The Superior Vena Cava: An Interesting Case Report - Soham Shah; Nityanand Thakur (Journal of Cardio-Thoracic Medicine, 2023)
Superior vena cava thrombosis with its extension into the right heart chambers can be commonly seen in the presence of chronically inserted catheters, coagulation disorders, malignancy, deep venous thrombosis (DVT), obesity, pregnancy, or trauma. Right atrial thrombi generally forms on injured endothelium due to implanted devices or foreign bodies, including tumors, pacemakers, and chronic right atrial catheters like triple-lumen catheters used for hemodialysis, giving chemotherapy, intravenous fluids or parenteral nutrition. It can lead to severe consequences, which may result in pulmonary or septic embolism and even systemic embolization as seen in the case of an atrial septal defect or patent foramen ovale. We report a case of a 49-year-old female who presented with complaints of mild to moderate dyspnea for 1 month with a past history of DVT and pulmonary embolism. She has undergone a gastric band procedure. Her imaging studies revealed a 42 x 20 mm intraluminal lesion within the Superior Vena Cava (SVC) extending into the right atrium. The patient's huge mass was removed by surgery, and pathological evaluation confirmed it to be thrombosis.